TIPOLOGI MASKULINITAS DALAM CERITA KARYA PENULIS ANAK INDONESIA SERI KECIL-KECIL PUNYA KARYA - Muizzu Nurhadi (Universitas 17 Agustus 1945 Surabaya, 2018)
Abstract. This research focusses on masculinity tipologies that is constructed by children writers in Kecil-Kecil Punya Karya’s series from their narrative structure. The research adopts isotopy’s concept by Greimas to reveal the masculinity tipologies from the text through relation between actant and story. The research uses Kecil-Kecil Punya Karya’s series about 2015-2016 that is written by children aged 7-12 and use male protagonist in the stories. There are three works that is suitable with the criterias, they are Untukmu Ayah (Rafid,2015), Matahari Pelangi (Rafid, 2015), dan Misteri Tengkorak Purbakala (Bagus, 2016). The result of the research shows that there are similarity perspectives in the masculinity forms that is written by the children writers. In addition, the children also show that they want to be part of society by showing they likes a man. Keywords: masculinities,children writers, isotopy